The girls from Ames : a story of women and a forty-year friendship - Zaslow, Jeffrey (Gotham Books, 2009)
Meet the Ames Girls: eleven childhood friends who formed a special bond growing up in Ames, Iowa. As young women, they moved to eight different states, yet managed to maintain an enduring friendship that would carry them through college and careers, marriage and motherhood, dating and divorce, a child<U+2019>s illness and the mysterious death of one member of their group. Capturing their remarkable story, The Girls from Ames is a testament to the deep bonds of women as they experience life<U+2019>s joys and challenges, and the power of friendship to triumph over heartbreak and unexpected tragedy--Publisher description.